Nidaros domkirkes korbuevegg. En arkitektonisk iscenesettelse av Olavskulten? - Ekroll, Øystein (Hikuin, 2017)
The choir screen wall of Nidaros Cathedral. An architectural staging of the cult of st. Olav? By Øystein Ekroll The site of the grave of St Olav (d.1030) was also the site of the high altar of Nidaros (Trondheim) Cathedral, and the shrine of the royal saint was placed above the grave and behind the high altar. The grave site became the fixed point in the cathedral’s history, and its architectural development was focused around this point. As the cathedral was gradually developed and extended, the line of the choir screen wall marking the boundary between the sacred area and the rest of the cathedral stayed immobile through the centuries. Three generations of the choir screen wall are known, ranging from the simple, wide opening of the late eleventh century via the elevated screen of c.1200 to the present magnificent screen that was constructed after the devastating fire of 1328 and probably completed before the Black Death struck Norway in 1349/50. The present screen contains several passages, niches and galleries that must have served liturgical purposes, most probably in connection with the Feast of St Olav in late July. In addition to the multitude of small sculptures there were also at least half a dozen of life-sized statues, all of which were destroyed by later fires. This paper suggests that the niches and galleries were used by singers during the large ceremonies, so that the wall became filled with ‘living statues’.